Neutrophil extracellular trap-associated carbamylation and histones trigger osteoclast formation in rheumatoid arthritis. Issue 5 (3rd February 2023) - O'Neil, Liam J; Oliveira, Christopher B; Wang, Xinghao; Navarrete, Mario; Barrera-Vargas, Ana; Merayo-Chalico, Javier; Aljahdali, Rwan; Aguirre-Aguilar, Eduardo; Carlucci, Philip; Kaplan, Mariana J; Carmona-Rivera, Carmelo
Abstract : Objective: Neutrophil infiltration into the synovial joint is a hallmark of rheumatoid arthritis (RA), a disease characterised by progressive bone erosion. However, the mechanisms by which neutrophils participate in bone destruction remain unclear. Carbamylation is a posttranslational modification linked to increased bone erosion in RA and we previously showed that carbamylation is present in RA neutrophil extracellular traps (NETs). However, it remains unclear whether NETs and their carbamylated protein cargo directly promote bone destruction and alter osteoclast biology. Methods: NETs and carbamylated NETs (cNETs) were assessed for their capacity to induce osteoclast formation in CD14+ monocytes. Chemical inhibitors and neutralising antibodies were used to elucidate the pathway by which NETs induce osteoclastogenesis. HLA-DRB1*04:01 mice received intra-articular injection of cNETs for 4 weeks. Joints were isolated and assessed for osteoclast formation. Plasma and synovial fluid samples from patients with RA (n=32) were assessed for the presence of carbamylated histone, and correlations to disease specific outcomes were performed. Results: We found that NETs, when cNETs, instruct monocytes to undergo rapid osteoclast formation. NET-mediated osteoclastogenesis appears to depend on Toll-like receptor 4 signalling and NET-associated proteins including histones and neutrophil elastase. In vivo, we identified that the number of osteoclasts increased following immunisation with cNETs in HLA-DRB1*04:01 transgenic mice. Furthermore, carbamylated histones are increased in plasma and synovial fluid from patients with RA and correlate with active bone resorption and inflammatory markers. Conclusions: Our results suggest that NETs have a direct role in RA-associated bone erosion by promoting osteoclast formation.